The Effect Of Interprofessional Communication Between Nurses, Laboratory Technicians, And Radiology Staff On Diagnostic Accuracy (The Review of Diabetic Studies, 2024)
Diagnostic accuracy is a cornerstone of patient safety and effective treatment, yet it remains vulnerable to errors, many of which originate in communication breakdowns. This research paper investigates the critical impact of interprofessional communication (IPC) among three pivotal groups in the diagnostic pathway: nurses, laboratory technicians, and radiology staff. Through a comprehensive literature review and analysis, the study delineates the interdependent roles of these professionals in a "diagnostic relay," where the baton of information and specimens is passed. It identifies and examines the common barriers that fracture these communication channels, including hierarchical silos, systemic pressures, technological fragmentation, and a lack of psychological safety. The paper directly links specific communication failures—such as mislabeled specimens, vague clinical histories, and passive critical result alerts—to tangible diagnostic inaccuracies and harmful delays. In response, the research evaluates structured frameworks for improvement, including SBAR protocols, standardized requisitions, and critical result policies, while arguing that technological solutions must be paired with a foundational cultural shift. Ultimately, the study concludes that optimizing IPC within this triad is not merely an administrative goal but a clinical imperative. Enhancing diagnostic accuracy requires a synergistic, multi-faceted strategy that integrates standardized tools, thoughtfully designed health information technology, and, most crucially, the cultivation of a collaborative culture characterized by psychological safety and shared responsibility.